2017
DOI: 10.1021/acs.iecr.6b04204
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Poly(lactic acid)/Metal–Organic Framework Nanocomposites Exhibiting Good Mechanical, Flame Retardant, and Dielectric Properties for the Fabrication of Disposable Electronics

Abstract: Nano metal–organic frameworks (ZIF-8) particles were synthesized, and poly­(lactic acid) (PLA)/ZIF-8 nanocomposite films were prepared by solution-blending and film-casting methods. The addition of nano ZIF-8 particles improved the mechanical properties and had an impact on the crystallization of PLA. The electrical properties of the PLA/ZIF-8 nanocomposites were found to be dependent on the frequency and the ZIF-8 content. The prepared PLA/ZIF-8 films had good transparency even as the content of the nano ZIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…For the ZIF‐8/EP composite, its PHRR and THR are 395 kw/m 2 and 30.8 MJ/m 2 , respectively, a decrease by 57 and 25.2% in comparison with pure EP, respectively. This may be attributed to the formation of nonflammable gases during the decomposition of organic ligand in ZIF‐8, which could dilute flammable gas and inhibit the combustion of EP composites . Meanwhile, the metal oxide generated in the combustion of the ZIF‐8/EP composites possesses a catalytic charring effect which could effectively improve the thermal stability of char residue .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ZIF‐8/EP composite, its PHRR and THR are 395 kw/m 2 and 30.8 MJ/m 2 , respectively, a decrease by 57 and 25.2% in comparison with pure EP, respectively. This may be attributed to the formation of nonflammable gases during the decomposition of organic ligand in ZIF‐8, which could dilute flammable gas and inhibit the combustion of EP composites . Meanwhile, the metal oxide generated in the combustion of the ZIF‐8/EP composites possesses a catalytic charring effect which could effectively improve the thermal stability of char residue .…”
Section: Resultsmentioning
confidence: 99%
“…At present, some researchers have tried to apply MOFs materials in the field of flame retardancy. Shi et al found that when 3 wt% ZIF‐8 was added into poly(lactic acid) (PLA), the LOI value of PLA/ZIF‐8 composites reached 26%, an increase by 5.5% in comparison with that of pure PLA, and its flame retardancy was improved . Hou et al found that, when 2 wt% Co‐MOF was added into PS, compared with pure PS, the PHRR and THR of the PS/Co‐MOF composites were decreased by 28.0% and 17.6%, and their flame retardancy was improved to some extent …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the char residue of PP‐5 contains element Zn, and the surface of the char residue is very smooth and compact as shown in Figures B and D. This shows that ZIF‐8 can effectively improve the structure of char layer, which is due to the facts that the Zn 2+ or ZnO from ZIF‐8 can capture macro radicals allowing recombination and leading to intermolecular crosslinking …”
Section: Resultsmentioning
confidence: 97%
“…The mixture was magnetically stirred at room temperature for 1 hour. The resultant particles were centrifuged, washed with CH 3 OH, and then dried in an oven at 80°C …”
Section: Experimental Programmementioning
confidence: 99%
“…In recent years, many researches about flame‐retardant PLA materials have been proposed . Among them, the most efficient flame‐retardant system for PLA is the combination of APP and the bio‐based charring agent such as lignin, starch, and β‐cyclodextrin (CD) .…”
Section: Introductionmentioning
confidence: 99%